การประเมินการอนุรักษ์พลังงานในบริษัทผลิตชิ้นส่วนรถยนต์ - Mongkoldhumrongkul, Krittaphas; Sukkanta, Phatcharapron; Jaikua, Mathin (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2020)
Assessment of Energy Conservation in the Auto Part Manufacturing Company Krittaphas Mongkoldhumrongkul, Phatcharapron Sukkanta and Mathin Jaikua รับบทความ: 15 มีนาคม 2563; แก้ไขบทความ: 18 มิถุนายน 2563; ยอมรับตีพิมพ์: 22 กรกฎาคม 2563 บทคัดย่อ การจัดทำมาตรการอนุรักษ์พลังงานจำเป็นต้องจัดทำอย่างเหมาะสมต่อการใช้พลังงานในแต่ละระบบ ทั้งนี้ผลลัพธ์อาจมีความแตกต่างกันไปตามการกำหนดมาตรการและวิธีการดำเนินมาตรการ โดยมักประเมินประสิทธิภาพการอนุรักษ์พลังงานจากผลประหยัดและระยะเวลาคืนทุน งานวิจัยนี้ต้องการหามาตรการอนุรักษ์พลังงานของบริษัทผลิตชิ้นส่วนรถยนต์ต้นแบบในระบบไฟฟ้าแสงสว่าง ระบบปรับอากาศ และระบบอัดอากาศ เพื่อเป็นแนวทางในการอนุรักษ์พลังงานรวมทั้งประเมินศักยภาพการลดการปล่อยก๊าซเรือนกระจกจากการเพิ่มประสิทธิภาพการใช้พลังงาน ผลการดำเนินงานพบว่าระบบปรับอากาศเป็นระบบที่มีการใช้พลังงานมากที่สุด การดำเนินมาตรการในระบบนี้จึงมีประสิทธิภาพมากที่สุด นอกจากนี้การดำเนินการตามมาตรการสามารถลดการใช้พลังงานของทุกระบบลงได้ 742,363.00 กิโลวัตต์–ชั่วโมงต่อปี คิดเป็นผลประหยัดประมาณ 2,665,083.10 บาทต่อปี ทั้งนี้ภาพรวมจากการอนุรักษ์พลังงานนี้สามารถลดการปลดปล่อยก๊าซคาร์บอนไดออกไซด์ได้ประมาณ 402.4744 ตันคาร์บอนไดออกไซด์เทียบเท่า งานวิจัยนี้จึงเป็นการช่วยลดภาวะโลกร้อนและนำไปสู่การเป็นสังคมคาร์บอนต่ำเพื่อการพัฒนาที่ยั่งยืน คำสำคัญ: การจัดการพลังงาน การอนุรักษ์พลังงาน ภาวะโลกร้อน สังคมคาร์บอนต่ำ ชิ้นส่วนรถยนต์ Abstract The energy conservation measures are needed to be appropriately implemented for individual system. However, the obtained measures may depend on the particular regulation and implementation applying on the system. The energy conservation efficiency is usually evaluated by the outcome of energy–saving and payback periods. This research aimed to discover energy conservation measures of the auto part manufacturing company in the lighting, the air conditioning, and the compressed air system, in order to conduct the measures for energy conservation and to assess the potential to reduce greenhouse gas emission while increasing the efficiency of energy consumption. After the measures was applied, the results revealed that the air conditioning system consumed highest amount of energy, thus the implemented measures exerted the most efficiently on this system. The implementation of the measures could entirely reduce energy use at 742,363.00 kilowatt–hours per year that had the value of 2,665,083.10 baht saving per year. Moreover, these implementations could reduce carbon dioxide emission approximately at 402.4744 tons of carbon dioxide equivalent. This research therefore helps in reducing global warming and leads to a low–carbon society for sustainable development. Keywords: Energy management, Energy Conservation, Global warming, Low–carbon society, Auto part